Associations Between Child Maltreatment Types and Pre- and Post-Partum Posttraumatic Stress Disorder Symptoms: A Brief Report - Frederickson, Alesha; Pigeon, Sereena; Hébert, Martine; Bernier, Annie; Frappier, Jean-Yves; Langevin, Rachel (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2023)
Objective: To foster resilience through reducing posttraumatic stress disorder (PTSD) symptoms in pregnant mothers with child maltreatment (CM) histories, it is important to understand factors impacting their well-being. This study explored whether CM predicted the severity of PTSD symptoms and symptom clusters during pregnancy and change in symptoms from pregnancy (Time 1; T1) to 3 months postpartum (Time 2; T2).Methods: 88 pregnant women (aged 18 to 29) completed surveys on CM exposure, adult interpersonal trauma experiences, and PTSD symptoms at T1; 58 participated at T2.Results: Stepwise regressions were conducted with the covariates age, family status, and adult interpersonal traumas. When accounting for all CM types, only neglect remained associated with overall PTSD symptoms (Ft1(4, 71) = 19.08, p < .001) and for each of the PTSD symptom clusters (ps < .01). Physical abuse remained associated with the alterations in cognition and mood cluster. No CM types were associated with changes in PTSD symptoms from T1 to T2.Implications: In future research, the implications of neglect for pregnant mothers should be explored in depth. Perinatal care should be trauma-informed, including assessing for CM histories, to foster greater resilience by reducing perinatal PTSD symptoms.